Towards the design of epitope candidates for Coronavirus 2 - Odhar, Hasanain Abdulhameed (Bioinformation, 2020)
The severe acute respiratory syndrome coronavirus-2, formerly known as 2019 novel coronavirus, is a pandemic public health threat. This beta coronavirus potentially infects the alveolar cells of the lung leading to pneumonia. The disease may progress into acute respiratory distress syndrome especially in elderly patients with comorbidities. Therefore, it is of interest to design and develop candidates for treatment, therapy and prevention. The spike glycoprotein of the virus known to potentially interact with angiotensin converting enzyme 2 as a cell entry receptor is a suitable candidate for further consideration as vaccine and treatment candidate. Hence, we screened the spike protein of coronavirus-2 for potential B-cell and T-cell epitopes for further deliberation. Thus, we document several peptides on the spike protein with predicted high antigenicity, low allergenicity and good stability against selected proteases. The linear B-cell epitope with sequence 'GFNCYFPLQSYGF' is of particular interest in this context towards the design and development of short peptide vaccine candidates for combat and care against the virus.